Analysis of Slang Word Formation in Itzy’s English Version Songs - Niken Larasati; Dian Wulandari (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research was intended to find out the forms and the most dominant of slang words are found in ITZY’s English Version Songs. The problems of the research are; what forms of slang words are found in the ITZY’s English Version songs and what the most dominant slang words that are used in the ITZY’s English Version songs. The method of this research is descriptive qualitative method. The theory that used for this research from Elisa Mattiello. The data of this research are slang words collected from lyrics in ITZY’s English Version Songs. The results of this research showed that there are 84 data and 5 types of slang word formation, such as 1 compounding, 1 suffixation, 28 blending, 35 clipping, and 19 variation. Besides, the type of slang word formations that most commonly used is clipping.